2015
DOI: 10.1260/1369-4332.18.5.687
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Linear and Nonlinear Behavior of Stiffened Steel Plate Shear Panels with Two Openings

Abstract: One of the main advantages of using Steel Plate Shear Panels (SPSPs) as lateral load resisting system is the ability to create openings at desired locations within the panels for access and architectural requirements. Stiffeners are used on the infill plate in order to achieve better structural performance and optimum utilization of the system's linear and nonlinear capabilities. Three 1/3rd scale specimens with two openings and with different separations, subjected to cyclic loads, were used to study the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In order to precisely determine the impacts of various opening types, positions, and opening ratios on the system strength, stiffness, ductility, and damping ratio of the SPSWs, various experimental and numerical investigations were carried out [19,32,39,42,[46][47][48][49][50][51] . H. Darvishi et al used numerical analysis to examine how various perforation ratios affected the behavior of the frame and the infill steel plate.…”
Section: Alterations In the System Strength Stiffness Ductility And D...mentioning
confidence: 99%
“…In order to precisely determine the impacts of various opening types, positions, and opening ratios on the system strength, stiffness, ductility, and damping ratio of the SPSWs, various experimental and numerical investigations were carried out [19,32,39,42,[46][47][48][49][50][51] . H. Darvishi et al used numerical analysis to examine how various perforation ratios affected the behavior of the frame and the infill steel plate.…”
Section: Alterations In the System Strength Stiffness Ductility And D...mentioning
confidence: 99%
“…The test results showed that the interval between the two openings had no effect on the structural parameters. Sabouri-Ghomi et al (2015) conducted experimental investigations on three stiffened SPSWs, each with two rectangular openings and with different separations. FE analysis was also undertaken to validate the theoretical approach using the new plate frame interaction method.…”
Section: Introductionmentioning
confidence: 99%
“…They assessed the proposed equation by analyzing a series of single-story perforated SPSWs with different aspect ratios and different perforation diameters. Sabouri-Ghomi et al (2015) experimentally studied the structural behavior of stiffened SPSWs with two rectangular openings and with different separations subjected to cyclic loads. Also, they determined the shear stiffness and ultimate shear strength of the SPSWs theoretically through the plate-frame interaction model.…”
Section: Introductionmentioning
confidence: 99%